2014
DOI: 10.1371/journal.pone.0088974
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Osteoclastogenic Activity of Praeruptorin A via Inhibition of p38/Akt-c-Fos-NFATc1 Signaling and PLCγ-Independent Ca2+ Oscillation

Abstract: BackgroundA decrease of bone mass is a major risk factor for fracture. Several natural products have traditionally been used as herbal medicines to prevent and/or treat bone disorders including osteoporosis. Praeruptorin A is isolated from the dry root extract of Peucedanum praeruptorum Dunn and has several biological activities, but its anti-osteoporotic activity has not been studied yet.Materials and MethodsThe effect of praeruptorin A on the differentiation of bone marrow–derived macrophages into osteoclast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 44 publications
0
26
0
Order By: Relevance
“…Phytochemical and pharmacological studies showed that angular-type pyranocoumarins are the major constituents of this plant [3][4][5][6][7][8][9], and these compounds have various beneficial effects such as anti-inflammatory [10][11][12], antiasthma [13], chemopreventive [14], smooth muscle relaxant [15], neuroprotective [16], and anti-osteoclastogenic properties [17].…”
Section: Introductionmentioning
confidence: 99%
“…Phytochemical and pharmacological studies showed that angular-type pyranocoumarins are the major constituents of this plant [3][4][5][6][7][8][9], and these compounds have various beneficial effects such as anti-inflammatory [10][11][12], antiasthma [13], chemopreventive [14], smooth muscle relaxant [15], neuroprotective [16], and anti-osteoclastogenic properties [17].…”
Section: Introductionmentioning
confidence: 99%
“…Here, IL‐7 decreased the phosphorylation of p38 and Akt without affecting JNK and ERK. It was demonstrated that the p38 signaling pathway has a direct involvement in mediating the induction of c‐Fos and NFATc1 during RANKL‐induced osteoclastogenesis (Yeon et al, ). A recent study showed that the Akt‐NFATc1 signaling axis has been known to play a critical role in osteoclast differentiation (Moriwaki et al, ), therefore the osteoclastogenic action of IL‐7/IL7R could activate the c‐Fos/c‐Jun pathway and up‐regulate NFATc1expression via the p38 and Akt signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Western blot and real-time PCR analysis were performed as described previously. 37 Primers for real-time PCR were chosen with the online Primer3 design program. 38 The primer sets used in this study are shown in Table 2.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%